Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1055/s-2002-32552
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antiplasmodial Activity of Tithonia diversifolia and Identification of its Main Active Constituent: Tagitinin C

Abstract: The antimalarial properties of Tithonia diversifolia, an Asteraceae traditionally used to treat malaria, were investigated in vitro against three strains of Plasmodium falciparum. The ether extract from aerial parts of the plant collected in São Tomé e Príncipe, demonstrated good antiplasmodial activity (IC 50 on FCA strain: 0.75 microg/ml). A bioassay guided fractionation of this extract led to the isolation of the known sesquiterpene lactone tagitinin C as an active component against Plasmodium (IC 50 on FCA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
66
0
5

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(81 citation statements)
references
References 5 publications
4
66
0
5
Order By: Relevance
“…As expected for a member of Asteraceae family, this species contains sesquiterpene lactones tagitinin A-C and F. Tagitinin C was reported as an active antiplasmodial component (0.33 µg/mL), which also possessed cytotoxic properties (IC 50 on HTC-116 cells: 0.706 µg/ mL) (Goffin et al 2002).…”
supporting
confidence: 58%
See 1 more Smart Citation
“…As expected for a member of Asteraceae family, this species contains sesquiterpene lactones tagitinin A-C and F. Tagitinin C was reported as an active antiplasmodial component (0.33 µg/mL), which also possessed cytotoxic properties (IC 50 on HTC-116 cells: 0.706 µg/ mL) (Goffin et al 2002).…”
supporting
confidence: 58%
“…The importance of this species as an antimalarial has been documented by many authors who found activity for the nonpolar and medium polarity extracts (Goffin et al 2002, Madureira et al 2002a, Elufioye & Agbedahunsi 2004.…”
mentioning
confidence: 88%
“…The tagitinin C, isolated and purified by Goffin et al [1], was employed for the preparation of standards. Its purity (97.2%) was determined by HPLC normalisation procedure [12].…”
Section: Reagentsmentioning
confidence: 99%
“…Goffin et al [1] isolated the tagitinin C ( Fig. 1), a known sesquiterpene lactone [2,3], from the aerial parts of the plant and discovered its antimalarial activity against Plasmodium falciparum.…”
Section: Introductionmentioning
confidence: 99%
“…This plant extracts are used for the treatment of malaria, diarrhea, fever, hepatitis and wounds (Gu et al, 2002, Cos et al, 2002. There are also attributed anti-inflammatory, amebic, antispasmodic, antifungal, antibacterial and antiviral activities (Goffin et al, 2002, Cos et al, 2002. Lu & co-workers (2000) in a research at Nanjing, China, observed the presence of 11 bioactive metabolites produced by Colletotrichum sp.…”
Section: Biological Activity From Medicinal Plants Endophytesmentioning
confidence: 99%